Strengthening Regional Food Security in East Java Through Agricultural Innovation: Evidence From a Dynamic Panel Analysis - Hapid Durohman,; Muhammad Yuka Anugrah,; Danial Muhammad Wirdyansyah, (Journal of Rural and Regional Innovation Studies, 2025)
This study examines how agricultural innovation contributes to regional food security in East Java, Indonesia, which is recognised as a National Food Barn. Using district level panel data from 38 regencies and municipalities covering the years 2015 to 2023, the analysis quantifies the effects of agricultural research and development (R&D) expenditure and the number of agricultural researchers on food security outcomes. Two complementary econometric approaches, namely bootstrapped Least Squares Dummy Variable estimation and the two step System Generalized Method of Moments, are applied to address unobserved heterogeneity and endogeneity. The results show that agricultural innovation significantly improves food security. An increase of one full time equivalent agricultural researcher raises average caloric consumption by 3.5 percent and reduces the prevalence of undernourishment by 2.8 percentage points. Similarly, higher agricultural R&D expenditure increases caloric adequacy by 2.0 percent and decreases child undernourishment by 1.8 percentage points. These findings confirm that investment in human capital within agricultural research produces stronger and more consistent effects than financial inputs alone. Policy implications suggest that strengthening local research capacity and maintaining R&D funding are essential for translating innovation into measurable improvements in food access and nutrition. Replicating successful initiatives across East Java’s 38 districts requires the establishment of district level agricultural innovation clusters that connect universities, research institutions, and farmer groups to accelerate technology dissemination.